New generation of organic scintillation materials - Budakovsky, S.V.; Galunov, N.Z.; Grinyov, B.V.; Kim, J.K.; Kim, Y.K.; Tarasenko, O.A. (Functional Materials, 2009)
Organic scintillation materials of the next generation have been designed and prepared, namely, organic polycrystals obtained from finely ground perfect single crystals by pressing and organic composite scintillators obtained by immersing crystalline grains into an optically transparent polymer matrix. The scintillation characteristics of proposed scintillation materials as detectors for short-range ionizing radiation and fast neutrons are discussed. This technology forms the base for production of large area detectors which can be used in devices for environmental radiation control, for security purposes (i.e. at customs to prevent the forbidden entry of fission materials), for various nuclear physical experiments, and in other branches of science and technology.